Pertanggungjawaban Hukum bagi Notaris dalam Membuat Akta Otentik Perspektif Pasal 65 Undang-Undang Nomor 2 Tahun 2014 tentang Jabatan Notaris - Yulianti, Elina Dyah; Anshari, Tunggul (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the aspects of legal accountability as well as formulate legal aspects of legal protection for notaries in making an authentic deed on the perspective of Article 65 of Law Number 2 of 2014 concerning the Notarial Department (UUJN). This type of research was normative juridical research (normative legal research) that used a statue approach and conceptual approach. This study was analyzed by grammatical and systematic interpretation methods. The results showed that the notary was fully responsible in the making of the official deed (willingly), while in the making of the deed the notary party was not fully responsible when it had carried out its duties and obligations to properly include (compile) the information of the parties into the deed. Protection for notaries in making authentic deeds, namely preventive legal protection in the form of UUJN, as well as repressive protection in the form of the provisions of Article 66 UUJN as a form of settlement efforts if the notary is in question before the law.